2015
DOI: 10.1089/jmf.2014.0120
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Assessment of Common Beans (Phaseolus vulgaris L.) Widely Consumed by Tunisian Population

Abstract: This research aimed at assessing the content and the functional properties of phytohemagglutinin (PHA) in different varieties of beans widely consumed in Tunisia through soaking, cooking, autoclaving, germination, and their combinations. This study was carried out on three varieties of white beans grown in different localities of Tunisia, namely Twila, Coco, and Beldia, as well as on imported and local canned beans. All bean samples underwent biochemical and immunological evaluation by employing several techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…The general suggestion is that the bacterial populations and changes in microbial community are dependent on the dose of PHA fed to animals. Hence, it seems reasonable to assume that 300 mg Beldia flour beans (~2.76 mg PHA/day) [41] employed in this research were sufficient enough to evoke a bacteriological response in the rat small intestine.…”
Section: Discussionmentioning
confidence: 98%
“…The general suggestion is that the bacterial populations and changes in microbial community are dependent on the dose of PHA fed to animals. Hence, it seems reasonable to assume that 300 mg Beldia flour beans (~2.76 mg PHA/day) [41] employed in this research were sufficient enough to evoke a bacteriological response in the rat small intestine.…”
Section: Discussionmentioning
confidence: 98%
“…Adeparusi et al found that autoclaving lima beans for 20 min eliminated all anti-nutrients except tannins [ 23 ]. Boiling of red and white kidney beans, notoriously rich in phytohemoggluttinin (PHA), also resulted in complete elimination of lectins [ 24 ]. Microwave ovens on the other hand, are not an effective method for lectin deactivation.…”
Section: Lectinsmentioning
confidence: 99%
“…In a preliminary study, the phytohemagglutinin present in white kidney beans ( Phaseolus vulgaris L.) variety Beldia, frequently consumed by Tunisian population (INRAT, Tunis, Tunisia), was characterized and some of its properties were described [ 28 ]. Biochemical and immunological evidence indicated that raw Beldia seeds contain elevated levels of bioactive lectins, approximately 9.20 g/kg [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary study, the phytohemagglutinin present in white kidney beans ( Phaseolus vulgaris L.) variety Beldia, frequently consumed by Tunisian population (INRAT, Tunis, Tunisia), was characterized and some of its properties were described [ 28 ]. Biochemical and immunological evidence indicated that raw Beldia seeds contain elevated levels of bioactive lectins, approximately 9.20 g/kg [ 28 ]. The raw Beldia beans demonstrated when orally administered to growing rats for 10 days at dose of 300 mg induced substantial modification of the morphology and physiological functions of the small intestine (i.e., disruption of absorption process) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%